Analisis nutrien campuran bungkil inti sawit dan onggok yang difermentasi dengan mikroba multikultur (Bacillus sp., Trichoderma sp., dan Cellulomonas sp.) - Didik Nur Edi; Osfar (Politeknik Negeri Jember, 2021)
This study aimed to evaluate nutrient content of palm kernel meal and cassava byproduct mixture fermented by using multicultural microbes (Bacillus sp., Trichoderma sp., and Cellulomonas sp.). Method used in this study was experiment using two treatments, namely BISTO (palm kernel meal and cassava by-product mixture before fermentation) and FBISTO (palm kernel meal and cassava by-product mixture after fermentation). Inoculum mixture of Bacillus sp. (2.56 x 109 CFU/ml), Trichoderma sp. (1.25 x 107 CFU/ml), and Cellulomonas sp. (2.80 x 106 CFU/ml) was used and the duration of the fermentation time was six days. Each three samples of BISTO and FBISTO were composited and analyzed for nutrient content. Data were analyzed descriptively by comparing nutrient content before and after fermentation. The results showed that the fermentation treatment by using multicultural microbes decreased organic matter, ether extract, and nitrogen-free extract. On the other hand, there were increased of crude protein, soluble protein, crude fiber, neutral detergent fiber, and acid detergent fiber. It could be concluded that the fermentation of palm kernel meal and cassava by-product mixture by using multicultural microbes could increase protein content, however, it was not effective to reduce fiber component.